Pengaruh Testimonial, Electronic Word Of Mouth (E-WOM) dan Shopping Lifestyle Terhadap Impulse Buying Gen Z pada Pengguna Tokopedia Palembang - Felix Melvin Pratama; Herry Widagdo (MDP Student Conference, 2026)
The rapid growth of business in Indonesia especially on e-commerce has significantly influenced consumer purchasing behavior, particulary on among generation z, who tend to enganged in impulse buying. This research aims to analyze the effect of testimonials, flash sales, electronic wrd of mouth, shopping lifestyle on impulse buying among generation z as users Tokopedia in Palembang city, this research adopt a quantitative approach with a casual research design. The sampling technique used is a cluster sampling, based on sub-dictrict areas in Palembang city, for the result is 200 respondens has aged 15-30 years who have previously made purchased on Tokopedia. Data were analyzed using multiple linear regressions with IBM SPSS software, the results is a variable testimonial, electronic word of mouth, shopping lifestyle have a positive and significant effect on impulse buying, while flash sale do not have a significant and positive effect. The adjusted R square vale is 38,2% that means independent variable explain 38,2% of the variation in impulse buying, while the remaining percentage is influence by other factors not examined in research.